Distribution of Ammonium-Oxidizing Bacteria in Sediment with Relation to Water Quality at the Musi River, Indonesia - Melki Melki; Alim Isnansetyo; Jaka Widada; Murwantoko Murwantoko (HAYATI Journal of Biosciences, 2018)
The Musi River is located in the southern Sumatra, Indonesia. Most of activities, i.e. agricultural, industrial, and urban activities are considered as being major sources of chemicals and nutrients with their waste products effluent into the river. Nitrification, the microbial oxidation of ammonia to nitrite and nitrate, occurs in a wide variety of environments and naturally remove anthropogenic N pollution. The purpose of this research was to determine of distribution of ammonium-oxidizing bacteria (AOB) in sediment with relation to water quality at the Musi river area. This study was conducted on rainy and dry season 2016 at five sampling sites from the freshwater to seawater at high and low tide conditions, the sampling sites are station St1 (Gandus), station St2 (Palembang city), station St3 (Upang), station St4 (Sungsang), and station St5 (Sea). Sediment samples were collected from the surface layer by using an Ekman grab. Some water quality such as salinity, temperature, pH, and dissolved oxygen (DO) were directly analyzed in the field, while other water quality such as NH4-N, NO2-N, and NO3-N were analyzed in the laboratory. The Density of AOB was determined by the most probable number of (MPN) method. The PCA was used to correlate variations of the AOB with physicochemical properties using software Xlstat. The results showed that the physicochemical properties had a range of salinity of 0 to 20 ppt, temperature of 29.21 to 31.82oC, pH of 4.88 to 7.93, DO of 3.44 to 11.33 mg/l, NH4-N in sediment of 0.04 to 0.87 mg/l, NO2-N in sediment of 0.01 to 1.77 mg/l, NO3-N in sediment of 0.09 to 2.08 mg/l. The density of AOB ranged from 7.2 x 102 to 6.1 x 103 cells/g sediment. Principal component analyses showed that temperature, pH, DO, and concentrations of nutrient contributed to density of AOB.